Examination on the choice of sport, selection and talent identification in the Hungarian literature - Dienes, B. I.; Bernáth, G. A.; Biró, M. (STADIUM - Hungarian Journal of Sport Sciences, 2020)
One of the main motives for finding and selecting talent is to ensure the long-term success of a sport. Fortunately, more and more professionals are researching the aspects of selection and the motives for choosing a sport. However, the issue of suitability is less well addressed. On the one hand, the study examines the motives of choosing a sport and the factors influencing it, as well as the question of success based on the results of Hungarian research.